PROFIL SKRINING INSPEKSI VISUAL ASAM ASETAT (IVA) PADA WANITA USIA SUBUR DI PUSKESMAS ALAK KOTA KUPANG TAHUN 2016 - Hironima Niyati Fitri (CHMK MIDWIFERY SCIENTIFIC JOURNAL, 2019)
Cervical cancer is the most cancer suffered by women in Indonesia. The International Agency for Research on Cancer (IARC) states that cervical cancer is a type of cancer in women who rank fourth in the world and rank number two after breast cancer. Cervical cancer is caused by Human Papiloma Virus (HPV) types 16 and 18 which are easily transmitted through unhealthy sexual intercourse and the infection occurs in 85% of women who have had sexual relations. This study aimed to know the profile of Visual Acetate (IVA) inspection screenings for Fertile Women (WUS) in the working area of ​​the Alak health center kupang city. This research is a quantitative study using a descriptive method with a population of 85 fertile women. Sampling using purposive sampling technique. The number of samples is 46 fertile women who have had sexual relations. This research was implemented in the working area of ​​the Alak health center kupang city The results showed that out of a total of 46 respondents who conducted IVA screening found 35 respondents showed Positive IVA with a lesion area of ​​<75%, 3 respondents showed positive results with a lesion area of> 75%, and 8 respondents showed negative results. Consider the importance of IVA examination, fertile women should routinely carry out IVA examinations so that they can detect early cervical cancer. . Keywords: IVA, Cervical Cancer